Mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material as well as preparation method and application thereof

By using a ternary solid waste system of ore powder-red mud-desulfurization gypsum in multi-source solid waste road grouting materials, it cooperates with fast hard sulfa-aluminate cement and water reducing agent to generate crystals with supportive effects, solving the problems of low compressive strength and complex raw material types in the existing technology, and achieving efficient industrial production and safe and environmentally friendly performance requirements.

CN119591373APending Publication Date: 2025-03-11XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411746089.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The stones of existing multi-source solid waste-based grouting gelling materials have low compressive strength and complex types of raw materials, making it difficult to achieve industrial continuous production.

Method used

The slurry composite system is constructed through the ternary solid waste system of red mud-red mud-desulfurization gypsum-based multi-source solid waste material, and the slurry composite system is constructed through the ternary solid waste system of red mud-orch-desulfurization gypsum, and the raw material content and concentration are scientifically controlled to generate crystals with supportive effects and improve the compressive strength and fluidity of stones.

Benefits of technology

The compressive strength of early and late stones of road grouting materials has been significantly improved, the fluidity and condensation time has been enhanced, the solid waste storage problem has been solved, and the preparation cost has been reduced, achieving safe, environmentally friendly and low-cost performance needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591373A_ABST
    Figure CN119591373A_ABST
Patent Text Reader

Abstract

The invention discloses a mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material as well as a preparation method and application thereof, and belongs to the technical field of solid waste utilization and road grouting reinforcement. The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material comprises a multi-source solid waste aggregate and 0.01-0.015 wt% of a water reducing agent mixed in the multi-source solid waste aggregate, wherein the multi-source solid waste aggregate is prepared from the following raw materials in percentage by weight: 40.5-43.5 wt% of red mud, 40.5-43.5 wt% of quick-hardening sulphoaluminate cement, 9-10 wt% of mineral powder and 3-10 wt% of desulfurized gypsum; the mass ratio of the red mud to the quick-hardening sulphoaluminate cement is 1: 1. The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material can be hydrated to generate spar with a supporting effect, so that the grouting material has high stone strength in an early stage and high stone strength stability in a later stage, and generated spar particles can interact with a water reducing agent; and meanwhile, the problem of stockpiling of contained solid wastes is effectively solved, and the preparation cost is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of solid waste utilization and road grouting reinforcement, and in particular relates to a mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material, a preparation method thereof, and an application thereof. Background Art

[0002] Grouting materials are filling materials that are injected into defective parts of road strata under pressure to achieve filling and consolidation effects. They can be divided into cement-based grouting materials and non-cement-based grouting materials according to the matrix. Among them, cement-based grouting materials are the most commonly used road grouting materials because of their good compatibility with the original road surface and their ability to better function. However, ideal road grouting materials also need to have the performance characteristics of short setting time, high early setting strength, stable later setting strength, high fluidity, simple preparation, safety, environmental protection and low cost. Therefore, it is very necessary to develop road grouting materials that can meet the above performance characteristics at the same time.

[0003] At present, related fields have prepared multi-source solid waste-based grouting cementitious materials with short setting time, high early strength and stable later strength by using red mud in conjunction with solid wastes such as slag, mineral slag, steel slag, desulfurized gypsum, and cement clinker. These materials can not only meet the performance requirements of most engineering applications, but also solve the storage problem of solid wastes such as red mud and reduce the preparation cost, and have broad application prospects.

[0004] However, the existing multi-source solid waste-based grouting cementitious materials as road grouting materials still have some shortcomings, such as: 1) the stone compressive strength is low, far from meeting the strength requirements for actual road use; 2) the raw materials are complex and numerous, and industrial continuous production is difficult. Summary of the invention

[0005] The present application discloses a mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material and its preparation method and application, which effectively solves the technical problems of low compressive strength and complex and numerous raw material types of existing multi-source solid waste-based grouting cementitious materials.

[0006] In order to achieve the above objectives, the technical solution adopted in this application is:

[0007] The first aspect of the present application provides a mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material, the raw materials of which include multi-source solid waste aggregate and 0.01-0.015wt% of a water reducer mixed in the multi-source solid waste aggregate;

[0008] The raw materials of the multi-source solid waste aggregates include:

[0009] Red mud 40.5-43.5wt%; Rapid hardening sulphoaluminate cement 40.5-43.5wt%;

[0010] Mineral powder 9-10wt%, desulfurized gypsum 3-10wt%;

[0011] Wherein, the mass ratio of the red mud to the rapid hardening sulphoaluminate cement is 1:1.

[0012] In a possible implementation scheme, the raw materials of the multi-source solid waste aggregate are:

[0013] Red mud 40.5wt%; Rapid hardening sulphoaluminate cement 40.5wt%;

[0014] Mineral powder 9wt%, desulfurized gypsum 10wt%;

[0015] or

[0016] Red mud 42.75wt%; Rapid hardening sulphoaluminate cement 42.75wt%;

[0017] Mineral powder 9.5wt%, desulfurized gypsum 5wt%;

[0018] or

[0019] Red mud 43.5wt%; Rapid hardening sulphoaluminate cement 43.5wt%;

[0020] Mineral powder 10wt%, desulfurized gypsum 3wt%.

[0021] In a possible embodiment, the chemical composition of the red mud includes: Fe2O3 29.22wt%, CaO2 0.61wt%, Al2O3 17.93wt%, SiO2 14.32wt%, Na2O 7.46wt%, TiO2 6.97wt%, MgO 0.82wt%, SO3 0.77wt%, K2O 0.19wt% and the remainder of impurities.

[0022] In a possible embodiment, the chemical composition of the mineral powder includes: CaO 42.32wt%, SiO2 26.15wt%, Al2O3 14.23wt%, MgO 7.47wt%, Fe2O3 3.38wt%, SO3 2.86wt%, TiO2 0.99wt%, K2O 0.33wt%, Na2O 0.33wt% and the remainder of impurities.

[0023] In a possible embodiment, the chemical composition of the desulfurized gypsum includes: SO3 54.34wt%, CaO 44.05wt%, SiO2 0.71wt%, Al2O3 0.35wt%, Fe2O3 0.23wt%, MgO 0.22wt%, Na2O 0.03wt% and the remainder of impurities.

[0024] In a possible implementation, the water reducer is a polycarboxylate water reducer or a naphthalene-based water reducer.

[0025] In a possible implementation scheme, the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material has the following performance parameters:

[0026] (1) The flow rate of the flow cone is 14.3-17.0s;

[0027] (2) The compressive strength of the stone is ≥7.12Mpa after 1 day, ≥15.55Mpa after 3 days, and ≥31.87Mpa after 28 days.

[0028] The second aspect of the present application provides a method for preparing the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material described in the present application, the preparation method comprising:

[0029] The step of mixing the raw material components in a dry state;

[0030] and, a step of adding water to the mixture obtained in the previous step to prepare a slurry.

[0031] In a possible embodiment, the water-cement ratio of the slurry is 0.44-0.48.

[0032] The third aspect of the present application provides the application of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material described in the present application in road-related projects.

[0033] Compared with the prior art, the advantages or beneficial effects of the present application include at least:

[0034] The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material provided in the present application constructs a slurry composite system by using a ternary solid waste system of red mud-mineral powder-desulfurized gypsum in coordination with fast-hardening sulphoaluminate cement and a water reducer, and scientifically controls the content concentration of the raw materials. On the one hand, it can generate supporting crystals during the hydration process, giving the road grouting material a high early stone strength, and the crystals have good stability, which can give the road grouting material a high stone strength stability in the later stage, so that the road grouting material can meet the actual road use standards as much as possible; on the other hand, the crystal particles can also interact with the water reducer, effectively increasing the fluidity of the road grouting material and shortening the coagulation time, so that the road grouting material has a moderate coagulation time and fluidity, effectively improving the actual use performance; thirdly, the road grouting material uses a large amount of red mud and a solid waste system of mineral powder and desulfurized gypsum, which not only solves the storage problem of the solid waste contained in the material, but also greatly reduces the preparation cost, effectively achieving the performance requirements of simple preparation, safety, environmental protection and low cost. Among them, the test results of the embodiment show that the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material of the present application has the following performance parameters: (1) the flow cone fluidity is 14.3-17.0s; (2) the water seepage rate is 0.2-0.31%; (3) the expansion rate is 0.005-0.009%; (4) the stone compressive strength after 1 day is ≥7.12Mpa, the stone compressive strength after 3 days is ≥15.55Mpa, and the stone compressive strength after 28 days is ≥31.87Mpa. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1 The XRD diffraction pattern of the hydration product of the best combination of quaternary solid waste aggregates provided in the embodiment of the present application;

[0037] Figure 2 This is a SEM image of the hydration product of the optimal combination of quaternary solid waste aggregates provided in the embodiments of the present application. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0039] In the following description of this specification, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the symbol " / " means "or".

[0040] In the following description of this specification, the term "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can mean any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.

[0041] In the following description of this specification, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or one after the other. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of this embodiment.

[0042] In the following description of this specification, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Any stated value or intermediate value in the stated range and any other stated value or each smaller range between the intermediate values ​​in the range are also included in this embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.

[0043] Unless otherwise specified, the technical / scientific terms used in this specification have the meanings commonly understood by those skilled in the art. Although this specification only describes preferred materials and methods, any similar or equivalent methods and materials may also be used in specific embodiments or test cases. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0044] In the first aspect, the embodiment of the present application provides a mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material. The raw materials of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material in the embodiment of the present application include multi-source solid waste aggregate and 0.01-0.015wt% of a water reducer mixed in the multi-source solid waste aggregate;

[0045] The raw materials of the multi-source solid waste aggregates include:

[0046] Red mud 40.5-43.5wt%; Rapid hardening sulphoaluminate cement 40.5-43.5wt%;

[0047] Mineral powder 9-10wt%, desulfurized gypsum 3-10wt%;

[0048] Wherein, the mass ratio of the red mud to the rapid hardening sulphoaluminate cement is 1:1.

[0049] It should be noted that the content of the water-reducing agent refers to the mass percentage of the water-reducing agent contained in every 100 parts of the multi-source solid waste aggregate, which may preferably be 0.01wt%, 0.012wt%, 0.015wt% or any one within the numerical range; at the same time, those skilled in the art understand that the sum of the contents of each raw material contained in the multi-source solid waste aggregate is 100%.

[0050] The embodiment of the present application constructs a slurry composite system by using a ternary solid waste system of red mud-mineral powder-desulfurized gypsum in conjunction with fast-hardening sulphoaluminate cement and a water reducer, and scientifically controls the content concentration of each raw material. On the one hand, it can generate supporting crystals during the hydration process, giving the road grouting material a high early stone strength, and the physicochemical stability of the crystals is relatively good, thereby giving the road grouting material a high stone strength stability in the later stage, so that the road grouting material can meet the actual road strength use standards as much as possible; on the other hand, the crystal particles can also interact with the water reducer, effectively increasing the fluidity of the road grouting material and shortening the setting time, so that the road grouting material has a moderate setting time and fluidity, and effectively improves the actual use performance; thirdly, the road grouting material uses a large amount of red mud and a solid waste system of mineral powder and desulfurized gypsum, which not only solves the storage problem of solid waste contained in the material, but also greatly reduces the preparation cost, effectively meeting the performance requirements of simple preparation, safety, environmental protection and low cost.

[0051] In an exemplary embodiment, the raw materials of the multi-source solid waste aggregate are preferably:

[0052] Red mud 40.5wt%; Rapid hardening sulphoaluminate cement 40.5wt%;

[0053] Mineral powder 9wt%, desulfurized gypsum 10wt%;

[0054] or

[0055] Red mud 42.75wt%; Rapid hardening sulphoaluminate cement 42.75wt%;

[0056] Mineral powder 9.5wt%, desulfurized gypsum 5wt%;

[0057] or

[0058] Red mud 43.5wt%; Rapid hardening sulphoaluminate cement 43.5wt%;

[0059] Mineral powder 10wt%, desulfurized gypsum 3wt%.

[0060] Of course, in addition to the examples described above, the raw material content of the multi-source solid waste aggregate may also include any combination within the optional range of the raw materials, which will not be described one by one in this specification; at the same time, the contents described in this specification are all measured in mass percentage.

[0061] It should be noted that the fast-hardening sulphoaluminate cement is mainly used as a proppant for the early compressive strength of stones, and can be commercially available fast-hardening sulphoaluminate cement of any source and chemical composition, and the present application embodiment has no special limitation on this. For example, the fast-hardening sulphoaluminate cement in the present application embodiment is taken from Shandong Zibo Yunhe Cement Co., Ltd., and its microscopic morphology is loose small particles, and the specific chemical composition is shown in Table 1.

[0062] Table 1: Chemical composition of rapid hardening sulphoaluminate cement (mass fraction, %)

[0063]

[0064] In the exemplary embodiment, the red mud is preferably Bayer red mud from Guangxi (Guangxi Branch of Aluminum Corporation of China Limited), and its microscopic morphology is loose particles stacked on each other. The specific chemical composition is shown in Table 2.

[0065] Table 2: Chemical composition of red mud (mass fraction, %)

[0066]

[0067] In the exemplary implementation, the mineral powder is preferably from Guangxi Yuansheng Slag Comprehensive Utilization Co., Ltd., and its microscopic appearance is uniformly distributed fine particles. The specific chemical composition is shown in Table 3.

[0068] Table 3: Chemical composition of mineral powder (mass fraction, %)

[0069]

[0070] In the exemplary implementation, the desulfurized gypsum is preferably from Guangxi Zhe Chuang Chemical Co., Ltd., and its microscopic morphology is layered small particles aggregated together. The specific chemical composition is shown in Table 4.

[0071] Table 4: Chemical composition of desulfurized gypsum (mass fraction, %)

[0072]

[0073] The present application uses the synergy of the solid waste system of red mud, mineral powder and desulfurized gypsum of the chemical composition, so that the raw material combination can generate a supporting spar skeleton complex during the hydration process, giving the road grouting material a high early stone strength, and the generated spar skeleton complex has relatively good structural stability, which can effectively solve the volume expansion problem of stones, give the road grouting material a high stone strength stability in the later stage, so that the road grouting material can meet the actual road strength use standards as much as possible. In addition, the particle characteristics of the selected red mud, mineral powder and desulfurized gypsum can give the surface of the complex a good adsorption effect on the water reducer, thereby effectively shortening the setting time while increasing the high fluidity of the prepared road grouting material.

[0074] In the exemplary embodiment, the water reducer is preferably a polycarboxylate water reducer or a naphthalene water reducer, and more preferably a polycarboxylate water reducer. In the embodiment of the present application, a polycarboxylate water reducer is added, so that the fluidity of the raw material particles can be improved by changing the electrostatic force on the surface of the raw material particles, and the original properties of the multi-source solid waste aggregate will not be significantly affected.

[0075] Based on the synergistic effect of the raw materials, the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material has the following performance parameters:

[0076] (1) The flow rate of the flow cone is 14.3-17.0s;

[0077] (2) The compressive strength of the stone is ≥7.12Mpa after 1 day, ≥15.55Mpa after 3 days, and ≥31.87Mpa after 28 days.

[0078] In a second aspect, the present application provides a method for preparing the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material described above, preferably comprising the steps of:

[0079] The step of mixing the raw material components in a dry state;

[0080] and, a step of adding water to the mixture obtained in the previous step to prepare a slurry.

[0081] In the exemplary embodiment, the water-cement ratio of the slurry is preferably 0.44-0.48, which can be 0.44, 0.45, 0.46, 0.47, 0.48 or any one in the range. In the embodiment of the present application, the water-cement ratio is controlled so that the road grouting material can be well compatible with the original road surface, which is conducive to better filling and consolidation.

[0082] In the third aspect, the embodiments of the present application provide the application of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material described in the present application in road-related projects. The road-related projects include but are not limited to grouting construction of road base or roadbed.

[0083] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0084] Example 1

[0085] This embodiment provides a mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material. The raw material composition of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material of this embodiment is 100 parts by mass of multi-source solid waste aggregate and 0.015 parts by mass of polycarboxylate water reducer. Among them, the multi-source solid waste aggregate raw material composition is:

[0086] 42.75 parts by mass of red mud; 42.75 parts by mass of rapid hardening sulphoaluminate cement;

[0087] 9.5 parts by mass of mineral powder and 5 parts by mass of desulfurized gypsum.

[0088] The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material is prepared according to the following steps:

[0089] After stirring and mixing the red mud, fast-hardening sulphoaluminate cement, mineral powder, desulfurized gypsum and polycarboxylate water-reducing agent in dry state, add them into a cement paste mixer together with water at a water-cement ratio of 0.45, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain the product.

[0090] Example 2

[0091] This embodiment provides a mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material. The raw material composition of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material of this embodiment is 100 parts by mass of multi-source solid waste aggregate and 0.015 parts by mass of polycarboxylate water reducer. Among them, the multi-source solid waste aggregate raw material composition is:

[0092] 40.5 parts by mass of red mud; 40.5 parts by mass of rapid hardening sulphoaluminate cement;

[0093] 9 parts by mass of mineral powder and 10 parts by mass of desulfurized gypsum.

[0094] The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material is prepared according to the following steps:

[0095] After stirring and mixing the red mud, fast-hardening sulphoaluminate cement, mineral powder, desulfurized gypsum and polycarboxylate water-reducing agent in dry state, add them into a cement paste mixer together with water at a water-cement ratio of 0.45, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain the product.

[0096] Example 3

[0097] This embodiment provides a mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material. The raw material composition of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material of this embodiment is 100 parts by mass of multi-source solid waste aggregate and 0.015 parts by mass of polycarboxylate water reducer. Among them, the multi-source solid waste aggregate raw material composition is:

[0098] 43.5 parts by mass of red mud; 43.5 parts by mass of rapid hardening sulphoaluminate cement;

[0099] 10 parts by mass of mineral powder and 3 parts by mass of desulfurized gypsum.

[0100] The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material is prepared according to the following steps:

[0101] After stirring and mixing the red mud, fast-hardening sulphoaluminate cement, mineral powder, desulfurized gypsum and polycarboxylate water-reducing agent in dry state, add them into a cement paste mixer together with water at a water-cement ratio of 0.45, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain the product.

[0102] Example 4

[0103] This embodiment provides a mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material. The raw material composition of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material of this embodiment is 100 parts by mass of multi-source solid waste aggregate and 0.01 parts by mass of polycarboxylate water reducer. Among them, the multi-source solid waste aggregate raw material composition is:

[0104] 42.75 parts by mass of red mud; 42.75 parts by mass of rapid hardening sulphoaluminate cement;

[0105] 9.5 parts by mass of mineral powder and 5 parts by mass of desulfurized gypsum.

[0106] The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material is prepared according to the following steps:

[0107] After stirring and mixing the red mud, fast-hardening sulphoaluminate cement, mineral powder, desulfurized gypsum and polycarboxylate water-reducing agent in dry state, add them into a cement paste mixer together with water at a water-cement ratio of 0.45, stir slowly for 120 seconds, stop for 15 seconds, and then stir quickly for 120 seconds to obtain the product.

[0108] Test Case

[0109] 1.1 In order to illustrate the actual performance of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material of the present application, the stone compressive strength, setting time, flow cone fluidity, water bleeding rate and expansion rate of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material prepared in each embodiment were tested according to GBT 17671-2021 cement mortar strength test method (ISO method), and the test results are described in Table 5.

[0110] Table 5: Performance test results of mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting materials

[0111]

[0112]

[0113] 1.2 In order to explore the synergistic effect between the raw materials contained in multi-source solid waste aggregates, the stone compressive strength is used as the evaluation standard, and the raw material composition and ratio of the multi-source solid waste aggregates are optimized through single factor experiments. The specific experiments are shown in Table 6.

[0114] Table 6: Raw material disassembly test of multi-source solid waste aggregates (mass percentage, wt%)

[0115]

[0116] According to Table 6, when the binary solid waste aggregate of the combination of rapid hardening sulfoaluminate cement and red mud is selected, the compressive strength decreases with the increase of red mud content, and the compressive strength is the highest when the maximum red mud content is 50%. Therefore, the red mud and rapid hardening sulfoaluminate cement are preferably combined in a ratio of 1:1; after adding mineral powder to the rapid hardening sulfoaluminate cement-red mud (1:1) combination system, the compressive strength further decreases with the increase of mineral powder content, and the compressive strength is the highest when the maximum mineral powder content is 10%. Therefore, the rapid hardening sulfoaluminate cement-red mud (1: 1) The maximum content of mineral powder that can be added to the combination system is preferably 10%, but it cannot meet the use requirements of road grouting materials due to its overall low compressive strength; when desulfurized gypsum is added to the ternary combination system of (fast-hardening sulphoaluminate cement-red mud (1:1))-mineral powder, the compressive strength is significantly enhanced and reaches the maximum year-on-year, but it gradually decreases with the increase in the amount of desulfurized gypsum added, so the content of desulfurized gypsum that can be added to the (fast-hardening sulphoaluminate cement-red mud (1:1))-mineral powder combination system is preferably 5%. Therefore, this application prefers a quaternary solid waste aggregate of (fast-hardening sulphoaluminate cement-red mud (1:1))-mineral powder-desulfurized gypsum, so that the compressive strength of the solid waste aggregate can be greatly improved on the basis of effectively improving the comprehensive utilization rate of solid waste. Among them, the best combination of quaternary solid waste aggregates is a combination of fast-hardening sulphoaluminate cement-red mud-mineral powder-desulfurized gypsum in a mass ratio of 42.75:42.75:9.5:5.

[0117] 1.2.1 In order to clarify the mechanism of the enhanced compressive performance of the quaternary solid waste aggregates in this application, this application provides the phase distribution of the hydration products of the best combination of quaternary solid waste aggregates. The results are Figure 1 As shown. Among them, Figure 1 The XRD diffraction pattern of the hydration products of the best combination of quaternary solid waste aggregates.

[0118] according to Figure 1 It can be seen that with the extension of the curing age, the diffraction peak of the desulfurized gypsum contained in the quaternary solid waste aggregate combination system gradually disappears from 1d to 28d, indicating that the desulfurized gypsum gradually dissolves in the quaternary solid waste aggregate combination system and participates in the reaction; the diffraction peak intensity of calcium sulfonate is relatively high from 1d to 28d, indicating that the amount of calcium sulfonate generated in the quaternary solid waste aggregate combination system is relatively large; the diffraction peak of hematite does not change significantly from 1d to 28d, indicating that it hardly participates in the reaction; the diffraction peak of calcite appears from 1d to 28d, indicating that there is a carbonization reaction in the quaternary solid waste aggregate combination system, and the carbon dioxide in the air reacts chemically with the calcium hydroxide in the quaternary solid waste aggregate combination system to generate calcium carbonate. This shows that the four raw materials contained in the quaternary solid waste aggregate combination system provided in the present application can react chemically after hydration and generate relatively stable compounds, which is beneficial to improving the stability of the compressive strength of the stone.

[0119] 1.2.2 This application also provides a microscopic morphology characterization diagram of the hydration product of the best combination of four-component solid waste aggregates. The results are Figure 2 As shown. Among them, Figure 2 This is the SEM image of the hydration products of the best combination of quaternary solid waste aggregates.

[0120] according to Figure 2 It can be seen that after hydration of quaternary solid waste aggregate for 1d, 3d and 28d, the hydration products are mainly long tube AF1 (calcium sulfoxide) and honeycomb CSH (calcium silicate hydrate). Among them, a large amount of calcium sulfoxide is generated at 1d of hydration, calcium silicate hydrate appears at 3d, and a large amount of calcium sulfoxide is still found at 28d of hydration, indicating that the hydration products during the period from 1d to 28d are mainly calcium sulfoxide crystals, and the skeleton support of calcium sulfoxide crystals plays an important role in early strength.

[0121] 1.3 In order to explore the influence of water reducer on the rheological properties and performance of road grouting materials, the following single factor test was used to optimize the dosage of water reducer, with fluidity and setting time as evaluation criteria and stone compressive strength as control criteria. The specific test and test results are shown in Table 7. In the test, the best combination of quaternary solid waste aggregates was selected for multi-source solid waste aggregates, and polycarboxylate water reducer was selected for water reducer.

[0122] Table 7: Water reducing agent content exploration test (mass percentage of water reducing agent in multi-source solid waste aggregate, wt%)

[0123]

[0124] According to Table 7, when the water reducer content is 0.01-0.015wt%, all technical indicators meet the technical requirements of road grouting materials; when the water reducer content is 0.02wt%, although the taper fluidity and setting time can also meet the required technical requirements, the compressive strength is significantly lower than the required technical requirements, indicating that the addition of water reducer can effectively improve the rheological properties of the prepared road grouting material, but will have a negative impact on the compressive performance. Therefore, the content of the water reducer is preferably 0.01-0.015wt% of the total mass of the multi-source solid waste aggregate.

[0125] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0126] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material, characterized in that: The raw materials include multi-source solid waste aggregates and 0.01-0.015wt% of a water reducing agent mixed in the multi-source solid waste aggregates; The raw materials of the multi-source solid waste aggregates include: Red mud 40.5-43.5wt%; Rapid hardening sulphoaluminate cement 40.5-43.5wt%; Mineral powder 9-10wt%, desulfurized gypsum 3-10wt%; Wherein, the mass ratio of the red mud to the rapid hardening sulphoaluminate cement is 1:

1.

2. The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material according to claim 1, characterized in that: The raw materials of the multi-source solid waste aggregate are: Red mud 40.5wt%; Rapid hardening sulphoaluminate cement 40.5wt%; Mineral powder 9wt%, desulfurized gypsum 10wt%; or Red mud 42.75wt%; Rapid hardening sulphoaluminate cement 42.75wt%; Mineral powder 9.5wt%, desulfurized gypsum 5wt%; or Red mud 43.5wt%; Rapid hardening sulphoaluminate cement 43.5wt%; Mineral powder 10wt%, desulfurized gypsum 3wt%.

3. The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material according to claim 1, characterized in that: The chemical composition of the red mud is: Fe2O3 29.22wt%, CaO 20.61wt%, Al2O3 17.93wt%, SiO2 14.32wt%, Na2O 7.46wt%, TiO2 6.97wt%, MgO 0.82wt%, SO3 0.77wt%, K2O 0.19wt% and the remainder of impurities.

4. The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material according to claim 3, characterized in that: The chemical composition of the mineral powder is: CaO 42.32wt%, SiO2 26.15wt%, Al2O3 14.23wt%, MgO 7.47wt%, Fe2O3 3.38wt%, SO3 2.86wt%, TiO2 0.99wt%, K2O 0.33wt%, Na2O 0.33wt% and the remainder of impurities.

5. The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material according to claim 1, characterized in that: The chemical composition of the desulfurized gypsum is: SO3 54.34wt%, CaO 44.05wt%, SiO2 0.71wt%, Al2O3 0.35wt%, Fe2O3 0.23wt%, MgO 0.22wt%, Na2O 0.03wt% and the remainder of impurities.

6. The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer or a naphthalene water reducer.

7. The mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material according to claim 1, characterized in that: It has the following performance parameters: (1) The flow rate of the flow cone is 14.3-17.0s; (2) The compressive strength of the stone is ≥7.12Mpa after 1 day, ≥15.55Mpa after 3 days, and ≥31.87Mpa after 28 days.

8. A method for preparing the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material according to any one of claims 1 to 7, characterized in that: Include: The step of mixing the raw material components in a dry state; and, a step of adding water to the mixture obtained in the previous step to prepare a slurry.

9. The preparation method according to claim 8, characterized in that: The water-cement ratio of the slurry is 0.44-0.

48.

10. Application of the mineral powder-red mud-desulfurized gypsum-based multi-source solid waste road grouting material according to any one of claims 1 to 7 in road-related projects.

Citation Information

Cited By

  • High-flow-state quick-setting early-strength cementing material as well as preparation method and application thereof

    CN120247437A

  • High-fluidity, fast-setting, and early-strength cementitious material, as well as its preparation method and application

    CN120247437B